Continuity, Confidence, Compassion and Culture: Lessons learned from Japanese midwives. (8th October 2014) - Shorten, Allison; Torigoe, Ikuyo; Weinstein, Lisa; Muto, Audrey
Abstract : Purpose: To explore midwifery practice through the eyes of Japanese midwives and midwifery students, with the aim of identifying traditional childbirth practices and models of midwifery care that lead to higher rates of physiologic birth as experienced by women in Japan. Research Questions: What specific cultural factors influence pregnancy care and childbirth practices in Japan? What factors and practices are associated with physiologic birth in Japan? How could traditional Japanese practices be utilized by midwives in the United States to improve birth outcomes? Significance: Despite its relationship with Western culture, Japan continues to promote physiologic birth without complications, at lower rates than many other developed nations. With a comparatively low cesarean rate of 18.6% in 2011 and one of the lowest maternal mortality rates in the world, cultural factors are clearly important. Recognition of traditional Japanese midwifery practices and unique models of midwifery care that can increase opportunities for physiologic birth have the potential to reverse the increasing trend for birth intervention in other countries. Methods: Mixed methods were used to explore midwifery practices in Japan. A pilot survey, translated into Japanese, was administered to midwives (n = 9) and midwifery students (n = 9) in 2 prefectures in Japan (one urban, one rural). Two focus groups were conducted to further explore culturally specific midwifery attitudes, practices, and future challenges in maintaining low birth‐intervention rates in Japan. Visits to hospital and community settings ( Josanin or birthing homes) enhanced understanding of described practices. Results: The prominent role of midwives in all low‐risk pregnancies in Japan was felt to increase opportunities for women to achieve physiologic birth. Interventions commonly used in the United States were reserved for complicated pregnancy. Japanese midwives recognized danger in increasing epidural use and the value of midwifery care in preventing unnecessary intervention. Important aspects of care included midwifery presence, compassion, confidence in women, non‐pharmacologic pain relief, movement/upright labor positions, and education provided by midwives. Discussion: Greater access to continuity of midwifery care in the United States could contribute to better birth outcomes. A larger study of Japanese midwives is planned to further explore effective practices that could be used in US settings to improve opportunities for physiologic birth.